UPAYA KONSERVASI EKOSISTEM MANGROVE BERBASIS KEMANDIRIAN MASYARAKAT DI WILAYAH PESISIR BATAM - Yarsi Efendi (SIMBIOSA, 2013)
Mangrove ecosystem in the coastal of Batam island has severe pressure due to the pace of development, they are activities of mangrove land conversion for development purposes such as shipyard industrial area, residential area, commercial area, tourism area, fish farming, illegal logging of mangrove wood for conventional charcoal industry for carbon, illegal logging of mangrove wood for use as scaffolds in physical development and even illegal logging mangrove wood flagpole for the benefit of political parties. The activities of the above has made the declining quality and quantity of mangrove ecosystems along the coast of Batam. this prompted the city government to do the restoration of mangrove ecosystem efforts. But recovery efforts are already underway to date have not shown significant results. There is no statistical data in the form of increase in mangrove area in Batam. According to our evaluation for mangrove ecosystem restoration program that has been done by the government, it can be concluded that one failure is not an active community participation. To achieve the success of recovery efforts in the area of coastal mangrove ecosystems among coastal area in Batam Island, the government should involve people's active participation as stakeholders in all stages of the mangrove ecosystem restoration program. Pattern recovery program topdown approach that had been done must be change to the peoples active participation.